Provjera osnovnih koncepata teorije privrženosti u okviru odnosa vlasnik-kućni ljubimac - Ombla, Jelena (Array, 2018)
The main purpose of this research was to test the applicability of the basic concepts of the attachment theory in the field of relationship between humans and their pets, i.e. to define the basic features of the aforementioned relationship in the context of attachment. The relationship between the owner and the pet is interpreted in the context of close relationships within a family, romantic and friendly domain. The survey included 219 dog owners, who were personally contacted and who agreed to fill in the questionnaire. The measuring instruments used in the questionnaire were as follows: Attachment Features and Functions Questionnaire, Modified Experiences in Close Relationships Inventory, Attachment to pets questionnaire. In a relationship with a pet, the function of separation anxiety before a safe haven is shown as an indicator of the attached behaviour. A relationship with a romantic partner is perceived by the dog owners as the one with the most powerful experience of a safe haven, while a relationship with a pet is perceived as the least powerful. Differences in the experience of separation anxiety between relationships are somewhat less evident, although they are present and support the leading status of a relationship with a romantic partner. A low degree of consistency among the dimensions of attachment in a relationship with humans and a relationship with a pet has been established. Individuals who are more inclined to avoid closeness and refuse intimacy are more likely to establish fewer attached behaviours in specific relationships (applies to all investigated types of relationships). The research has contributed to defining the characteristics of the relationship between the owner and the pet since it includes the presumed role of the attachment in such a relationship. Generally, the results point towards the conclusion in the theoretically expected direction, which is that the relationship with the pet relates to the remaining three close inte